The Influence of Acne Vulgaris Severity on Social Appearance Anxiety and Quality of Life in Undergraduate Students of Universitas Padjadjaran, Bandung, Indonesia - Ghossanidewi, Raden Aura Tsabita Hazna; Ruchiatan, Kartika; Puspitosari, Diah; Hindritiani, Reti; Rakhmilla, Lulu Eva (Journal of Pakistan Association of Dermatologists, 2023)
Introduction. Acne vulgaris (AV) has an important effect on physical appearance, which can cause psychological problems. The purpose of this study was to determine the effect of the severity of acne vulgaris on social appearance anxiety and quality of life (QoL) in undergraduate students at Universitas Padjadjaran in Bandung, Indonesia. Method. This research was conducted using an analytic observational method with a cross-sectional approach. We enrolled 259 students who met inclusion criteria and gave consent to be diagnosed by dermatologists through their facial photography. This study used the Social Appearance Anxiety Scale (SAAS) and the Cardiff Acne Disability Index (CADI). The Kruskal-Wallis test analyzed different acne severity groups’ mean and standard deviation. Results. Out of 259 students, 90 had mild acne, 84 had moderate acne, and 85 had severe acne. All participantsâ€™ mean age of acne sufferers is 19.80 years old and more common in females (76.45%). The moderate acne group had the highest mean SAAS compared to students with mild and severe acne (mean 44.21; CI: 41.47-46.96; p<0.005). The median CADI value in college students with severe acne falls into the mildly to moderately impaired QoL category (median 6 (0-14), p<0.005). Conclusion. This study showed that the severity of acne vulgaris influences social appearance anxiety and QoL in students. The study results are expected to add information for clinicians about the psychological impact on acne patients as a consideration for AV treatment. Social support may affect social appearance anxiety and QoL, which affect the acne sufferers’ SAAS and CADI scores.